Modelagem hidrológica apoiada por sistema de informações geográficas - Gilcimar Pires Cabral Oliveira (2015)
The representation of the phenomena and processes that rule the natural systems has been propitiating opportunities for the development of models that aim showing the behavior of these systems. In this context, the hydrologic models can be highlighted as they aim to understand the physical processes of the hydrologic cycle at its temporaldimension. Frequently, the main data for the hydrologic modeling have been used based in the experience and sensibility of the analysts or hydrologists or, even, based in data from other studies. The present study had the objective to discuss the potential use of Geographic Information Systems GIS for the processing of data and georeferenced information to obtain the main parameters for the hydrologic modeling. In this work the modeling is performed in Soil Moisture Accounting Procedure Model SMAP. With the support of the GIS tools, it was possible to obtain an accurate model, with good results between the values of calculated and observed flows, taking to a good determination coefficient. From the obtained results, with the integration of the GIS tools to hydrologic models, the main conclusion of this study relates to the efficacy ofthe use of these systems as a support for the estimation of entrance parameters for the modeling process, in the case of the studied basins.